LEGAL TRANSFORMATION IN THE AGE OF ARTIFICIAL INTELLIGENCE: A LITERATURE REVIEW ON REGULATORY, ETHICAL AND DATA PROTECTION CHALLENGES IN INDONESIA - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2026)
The exponential development of artificial intelligence (AI) has created a fundamental disruption to the national legal order, demanding regulatory transformation that is adaptive to algorithmic autonomy, ethical issues, and the protection of personal data. This article aims to analyse the legal challenges faced by Indonesia in the AI era through a literature review using a juridical-normative approach and content analysis. The research findings indicate that Indonesia faces a specific regulatory vacuum (legal vacuum) that creates legal uncertainty, particularly regarding liability for discriminatory or harmful AI decisions resulting from the lack of transparency associated with the ‘black box’ problem. Fragmented inter-institutional authority and the regulatory body’s lack of technical expertise exacerbate the situation, whilst the implementation of Law No. 27 of 2022 on Personal Data Protection (PDP Law) faces technical dilemmas regarding data minimisation, informed consent, and the right to erasure within machine learning systems. From an ethical perspective, algorithmic bias has the potential to perpetuate structural discrimination that runs counter to the values of Pancasila, whilst the absence of an obligation to label synthetic content threatens the integrity of public information. This article recommends the enactment of a dedicated AI law adopting the principle of strict liability, strengthening the capacity of the Personal Data Protection Agency, formulating operational AI ethics grounded in Pancasila, and implementing a hybrid legal approach combining hard law with soft law. This legal transformation is an absolute prerequisite for Indonesia to harness the potential of AI for Indonesia Emas 2045 without compromising human rights, social justice, and the nation’s digital sovereignty.